Between Normative Doctrine and Social Reality: Reinterpreting Kafa'ah in Indonesian Islamic Marriage Practices - Asman Asman; Mohamed Aamer (STAI Syekh Abdur Rauf, Aceh Singkil, 2026)
The concept of kafa'ah in marriage is an important principle in Islamic family law, emphasizing equality between prospective husband and wife. In Muslim social practices, this concept is not only understood from a normative-religious perspective but is also influenced by social, cultural, economic, and social status dynamics. This study aims to analyze the concept of kafa'ah from a socio-legal perspective by examining the relationship between Islamic legal norms and the social realities of marital practice. The method used is a qualitative approach with a juridical-sociological approach, examining legal norms in Islamic jurisprudence literature, legislation, and the social practices of Muslim communities. The results show that classically, kafa'ah encompasses equality in religion, lineage, social status, profession, and economic capacity. Scholars of various schools of thought have differing views regarding these elements, but generally place shared religion and moral commitment as key aspects. From a socio-legal perspective, the application of this concept has undergone transformation along with changes in social structures and the development of modern values, leading to a shift in traditional aspects such as lineage and social status. National law, through the Compilation of Islamic Law, emphasizes harmony and concord without explicitly regulating kafa'ah (comparative agreement). The resulting policy implications highlight the need for a reformulation of Islamic family law guidelines that are adaptive to social dynamics, emphasizing psychological, economic, and religious compatibility. Furthermore, religious courts need to integrate a socio-legal approach into their practice through contextual technical guidelines. This research is expected to contribute to the development of responsive Islamic family law studies. [Konsep kafa’ah dalam perkawinan merupakan prinsip penting dalam hukum keluarga Islam yang menekankan kesetaraan antara calon suami dan istri. Dalam praktik sosial masyarakat Muslim, konsep ini tidak hanya dipahami secara normatif-keagamaan, tetapi juga dipengaruhi oleh dinamika sosial, budaya, ekonomi, dan status sosial. Penelitian ini bertujuan menganalisis konsep kafa’ah melalui perspektif sosio-legal dengan menelaah keterkaitan antara norma hukum Islam dan realitas sosial dalam praktik perkawinan. Metode yang digunakan adalah pendekatan kualitatif dengan jenis penelitian yuridis-sosiologis, yaitu mengkaji norma hukum dalam literatur fikih, peraturan perundang-undangan, serta praktik sosial masyarakat Muslim. Hasil penelitian menunjukkan bahwa secara klasik, kafa’ah mencakup kesetaraan dalam agama, nasab, status sosial, profesi, dan kemampuan ekonomi. Para ulama mazhab memiliki perbedaan pandangan terkait unsur-unsur tersebut, namun secara umum menempatkan kesamaan agama dan komitmen moral sebagai aspek utama. Dalam perspektif sosio-legal, penerapan konsep ini mengalami transformasi seiring perubahan struktur sosial dan perkembangan nilai modern, sehingga aspek tradisional seperti nasab dan status sosial mulai bergeser. Hukum nasional melalui Kompilasi Hukum Islam menekankan keserasian dan keharmonisan tanpa mengatur kafa’ah secara eksplisit. Implikasi kebijakan yang muncul adalah perlunya reformulasi pedoman hukum keluarga Islam yang adaptif terhadap dinamika sosial, dengan menekankan kompatibilitas psikologis, ekonomi, dan keagamaan. Selain itu, peradilan agama perlu mengintegrasikan pendekatan sosio-legal dalam praktiknya melalui pedoman teknis yang kontekstual. Penelitian ini diharapkan berkontribusi dalam pengembangan kajian hukum keluarga Islam yang responsif.]